OP06 Multi-method development of new ambulance service quality and performance measures. Issue 10 (28th September 2017) - Coster, Joanne; Siriwardena, A Niroshan; Turner, Janette; Jacques, Richard; Crum, Annabel; Nicholl, Jon
Abstract : Background: The scope to measure the quality and performance of ambulance service care is limited by poor access to follow up patient information and lack of consensus about what to measure. The Prehospital Outcomes for Evidence Based Evaluation (PhOEBE) research programme aims to address these research gaps by identifying potentially important prehospital quality measures and testing these using a prehospital/linked subsequent health service dataset. Methods: We undertook systematic reviews of published and aspirational measures, together with interviews with ambulance service users to identify potential measures. Measures identified from reviews and interviews were prioritised using a multi-stakeholder consensus conference. Measures identified as high priority were further refined and ranked through an expert Delphi method and a service user/patient public involvement workshop. High ranking measures were further assessed against criteria for good outcome measures, including feasibility, importance and relevance, to create a shortlist of measures. Results: Eight high-ranking measures were shortlisted following assessment against criteria for good outcome measures. These were: Mean reduction in pain score Proportion of serious emergency conditions correctly identified Average response time (mean/median) Proportion of non-conveyance decisions which resulted in admission or death within 3 days (hear and treat and see and treat) Proportion of patients with a low risk of death, who subsequently die within 3 days of an ambulance contact Proportion of ambulance patients with a serious emergency condition who survive to admission, and to 7 days post-admission Proportion of unnecessary transports to ED Proportion of cases with a specific condition treated in accordance with established protocols and guidelines, e.g. stroke, diabetes, falls Conclusion: These measures can be used to assess the impact of care provided by the ambulance service and to support quality improvement through monitoring, audit and service evaluation. Some measures are based on ambulance service data only whereas others require additional linked hospital data.